DESIGN OF ROAD GEOMETRIC WITH AUTOCAD® CIVIL 3D: A CASE JALAN KERTAWANGUNAN–KADUGEDE, KUNINGAN-INDONESIA - Pebri Tri Anugraha; Yusra Aulia Sari; Adinda Fajarika (LEADER: Civil Engineering and Architecture Journal, 2024)
In today's globalized world, much software is developed to make work easier to implement. This software is demonstrated using AutoCAD Civil 3D® to demonstrate how geometric road design can be completed briefly. In this case, the purpose of geometric planning is to evaluate the effectiveness of manual geometric planning using AutoCAD Civil 3D®. This journal's geometric road planning implements qualitative methods. The geometric planning of the road that became the subject of this journal's research is located on Jalan Kertawangunan - Kadugede, with a road plan length of 9.3 km as an additional alternative to Kuningan Regency's new outer ring road. The calculation of horizontal alignment required the minimum bend (Rmin) and transition arch (Ls) values. Therefore, it is necessary to plan the assembly ahead of time before planning the corridor. The corridor's function is to determine the location of cut and fill based on road planning. As a result, planning a path with AutoCAD Civil 3D® is more effective and efficient, and it can retrieve the necessary data quickly. There are four points of interest with different types of curves in road traffic planning. The plan speed (Vr) was set to 60 km/h, the maximum superelevation slope (e-maks) was set to 0.08, and the transverse friction coefficient (f) was set to 0.153. The average excavation volume obtained from this planning is approximately 1,900,000 m3